2020
DOI: 10.1007/s10803-019-04343-z
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Notion of Autism Spectrum Conditions: A Cross-Cultural Study

Abstract: Cultural background might influence knowledge and attitudes regarding autism, influencing willingness to interact. We studied whether beliefs, knowledge, contact, and attitude differed between the UK and Malaysia. With mediation analyses, we studied how these factors influenced willingness to interact. Autism was more often linked to food in the UK, and to upbringing in Malaysia. Knowledge, contact, and acceptance were greater in the UK. When excluding psychology students, Malaysian students were less willing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Exposure to and acceptance of neurodiversity is one such factor that may influence these beliefs. Indeed, given the existence of cross-cultural differences in attitudes and stigma towards autism and disability (de Vries et al, 2020 ; Gillespie-Lynch et al, 2019 ; Someki et al, 2018 ), interventionists may sometimes face the challenging task of respecting clients’ cultural beliefs while also encouraging caregivers to embrace a neurodiversity-aligned perspective. The first step in this process is for clinicians and researchers to develop their own cultural awareness and acknowledge their own personal biases (Fong et al, 2016 ).…”
Section: Improving the Alignment Of Ndbis With Neurodiversitymentioning
confidence: 99%
“…Exposure to and acceptance of neurodiversity is one such factor that may influence these beliefs. Indeed, given the existence of cross-cultural differences in attitudes and stigma towards autism and disability (de Vries et al, 2020 ; Gillespie-Lynch et al, 2019 ; Someki et al, 2018 ), interventionists may sometimes face the challenging task of respecting clients’ cultural beliefs while also encouraging caregivers to embrace a neurodiversity-aligned perspective. The first step in this process is for clinicians and researchers to develop their own cultural awareness and acknowledge their own personal biases (Fong et al, 2016 ).…”
Section: Improving the Alignment Of Ndbis With Neurodiversitymentioning
confidence: 99%
“…An emerging body of cross-cultural research suggests that public autism stigma, measured by desired social distance with autistic individuals, is heightened in South Korea (Kim et al, 2021 ), Japan (Someki et al, 2018 ), Lebanon (Obeid et al, 2015 ), and Malaysia (de Vries et al, 2020 ) compared to the US or UK. This cross-cultural pattern aligns with speculation that stigma more generally may be higher in more collectivistic (i.e., prioritizing group harmony and cohesion) than individualistic (i.e., prioritizing independence and individual success) cultures (e.g., Papadopoulos et al, 2013 ).…”
mentioning
confidence: 99%
“… 10 Thirdly, culture affects people’s knowledge of and attitude towards ASD. 11 Stigma in collectivist cultures, like the one in Malaysia, seems to be more prevalent compared to individualist cultures, like those in many Western countries. 12 Finally, awareness of ASD is still comparatively low in the former region and a review of literature has shown that there have been limited studies on stigma and ASD conducted in South-East Asia, particularly in Malaysia.…”
Section: Introductionmentioning
confidence: 99%